Mapping the terrain: A conceptual schema for a mental health medication support service in community pharmacy - Scahill; Fowler, J.; Hattingh, H. Laetitia; Kelly, F.; Wheeler, A. (SAGE Publications, 2015)
Objective: Mental health–related problems pose a serious issue for primary care, and community pharmacy could make a significant contribution, but there is a dearth of information. Methods: This article reports synthesis of the literature on mental health interventions across a range of pharmacy models, and pharmacy services in contexts beyond mental health. To best inform the design of a community pharmacy medication support intervention for mental health consumers, the literature was reported as a conceptual schema and subsequent recommendations for development, implementation and evaluation of the service. A broad conceptualisation was taken in this review. In addition to mental health and community pharmacy literature, policy/initiatives, organisational culture and change management principles, and evaluative processes were reviewed. Key words were selected and literature reviews undertaken using EMBASE, PubMed, CINAHL and Web of Science. Results: Recommendations were made around: medication support intervention design, consumer recruitment, implementation in community pharmacy and evaluation. Surprisingly, there is a scarce literature relating to mental health interventions in community pharmacy. Even so, findings from other pharmacy models and broader medicines management for chronic illness can inform development of a medication support service for mental health consumers. Key learnings include the need to expand medicines management beyond adherence with respect to both intervention design and evaluation. Conclusion: The conceptual framework is grounded in the need for programmes to be embedded within pharmacies that are part of the health system as a whole.